Bibliometric Analysis of Citation Patterns in Korean Kinesiology Research - Danielle Lee (Korea Institute of Sport Science, 2022)
PURPOSE The purpose of this study is to analyze various citation patterns such as the scope and intensity of the academic influence of Korean "Kinesiology" studies. METHODS To this end, this paper collected and analyzed 17,693 target articles published in 22 KCI-accredited "Kinesiology" related journals from 2001 to 2014, and 98,941 citing cases that took advantage of target articles as references. Specifically, this paper analyzed the citation pattern by dividing it into two parts. First, this paper analyzed the distribution of citations in individual target articles and the top-cited articles and top-cited researchers. Second, this paper also analyzed the citing articles; such as in which journal, what academic field, and in what pattern the "Kinesiology" target articles were cited. RESULTS As a result, 15% of the target articles were not cited at all for five years after publication, while 6.8% of papers were cited more than 17 times, which was exceptionally more cited compared to the majority of target articles. There were no research topics exclusively exerting influence in Korean "Kinesiology" research, but relatively many cited thesis topics include 'self-management, 'leisure statement', 'psychological well-being', 'self-confidence', 'service quality', and 'leisure flow'. Besides, the Korean "Kinesiology" articles accounted for 76% of the total of about 98,000 citations, having greater influence within the same academic field than other academic fields. CONCLUSIONS This study contributes to the relevant literature in that it is one of the early endeavors to study the citation pattern for the entire Korean kinesiology articles.